Above‐ground and below‐ground Salix dynamics in response to river processes. Issue 20 (2nd September 2013) - Pasquale, N.; Perona, P.; Francis, R.; Burlando, P.
Abstract Riparian vegetation influences hydraulic and morphodynamic river processes and may contribute to sediment stabilization. In turn, vegetation recruitment and growth on non‐cohesive fluvial deposits strongly depends on river hydrology and the ability of roots to develop and to anchor efficiently to resist flow erosion. In this paper, we examine the above‐ground and the below‐ground seasonal growth dynamics of Salix cuttings in relation to local river hydrodynamics and morphodynamics, on the basis of a detailed and unique data set. During the two season‐long campaigns in 2009 and 2010, 1188 and 1152 cuttings, respectively, were organized in square plots and planted on a gravel island of the restored reach of the River Thur (Neunforn, Thurgau, Switzerland). Each year, all cuttings were monitored almost regularly from the beginning until the end of the growing season (April–September). Root development statistics were also obtained from high‐resolution scanner analysis of carefully uprooted samples from selected plots. Our results show how cutting survival and the nature and strength of correlations between island topography and cutting growth statistics depend on river hydrology. An empirical functional form that links root development based on the measured main stem length is then proposed for predictive purposes. Cutting mortality following flood events is shown to depend nonlinearly on both erosion and deposition processes, whereas it appears more linearly related to the magnitude of the bed shear stress distribution generated by the maximum seasonal flood. This analysis allows an identification of an important threshold for plant survival within different erosion and deposition regimes, which explains the spatial and temporal distribution of the surviving cuttings within the plots. These results have practical implications, for instance, for evaluating, planning and managing the use of riparian trees in restoration projects. Copyright © 2013 John Wiley & Sons, Ltd.